Prevalence and factors associated with mental health challenges among adolescents with HIV and viral non-suppression in rural northern Uganda - Kwesiga, Jeremiah Mutinye; Namuli, Justine Diana; Akimana, Benedict; Serunjogi, Joyce Nalugya; Kitaka, Sabrina Bakeera; Seggane, Musisi; Kaleebu, Pontiano; Nyirenda, Moffat; Nakimuli-Mpungu, Etheldreda (Frontiers in Public Health, 2025)
IntroductionAdolescents living with HIV (ALWH) face significant mental health challenges, such as depression and anxiety, which negatively impact their HIV treatment outcomes. This study investigated the prevalence and factors associated with mental health challenges among adolescents with unsuppressed viral loads in Northern Uganda.MethodsIn 2021, 121 dyads of caregivers and ALWH (10 to 18 years) with unsuppressed viral loads were recruited from five community-based HIV clinics in Kitgum district. They were assessed for mental health challenges using the Revised Child Anxiety and Depression Scale (RCADS-25), the Patterson Suicide Risk Assessment Tool and the Clinician-administered Post-traumatic Stress Disorder Scale for Children and Adolescents (CAPS-CA). Bivariate and multivariate analysis of the data was carried out using STATA version 18.ResultsEmotional problems were observed in 61.97% of participants. Among these, depression was present in 45.45% of individuals, and all participants diagnosed with depression also exhibited significant comorbid anxiety symptoms. Notably, 16.52% of participants experienced anxiety without comorbid depression. Having food security (OR = 0.03; p = 0.003), and the absence of recurrent infections (OR = 0.47; p = 0.023) were protective against mental health challenges. However, significant post-traumatic stress symptoms were independently associated with mental health challenges (OR = 1.33; p < 0.0001). No significant association was observed between emotional problems and gender (χ2 = 0.009; p = 0.94).ConclusionThese results emphasize the importance of addressing underlying socio-economic and psychological factors to improve mental health well-being. Targeted interventions focused on reducing barriers to resources and providing mental health support are essential for fostering equitable mental health outcomes.